Suppression of Photosynthetic Gene Expression in Roots Is Required for Sustained Root Growth under Phosphate Deficiency . Issue 3 (27th May 2014) - Kang, Jun; Yu, Haopeng; Tian, Caihuan; Zhou, Wenkun; Li, Chuanyou; Jiao, Yuling; Liu, Dong
Abstract : Functional disruption of tyrosylprotein sulfotransferase in Arabidopsis activates photosynthetic gene expression in roots and enhances inhibition of root growth under phosphate deficiency . Abstract: Plants cope with inorganic phosphate (Pi ) deficiencies in their environment by adjusting their developmental programs and metabolic activities. For Arabidopsis ( Arabidopsis thaliana ), the developmental responses include the inhibition of primary root growth and the enhanced formation of lateral roots and root hairs. Pi deficiency also inhibits photosynthesis by suppressing the expression of photosynthetic genes. Early studies showed that photosynthetic gene expression was also suppressed in Pi -deficient roots, a nonphotosynthetic organ; however, the biological relevance of this phenomenon remains unknown. In this work, we characterized an Arabidopsis mutant, hypersensitive to Pi starvation7 ( hps7 ), that is hypersensitive to Pi deficiency; the hypersensitivity includes an increased inhibition of root growth. HPS7 encodes a tyrosylprotein sulfotransferase. Accumulation of HPS7 proteins in root tips is enhanced by Pi deficiency. Comparative RNA sequencing analyses indicated that the expression of many photosynthetic genes is activated in roots of hps7 . Under Pi deficiency, the expression of photosynthetic genes in hps7 is further increased, which leads to enhanced accumulation of chlorophyll, starch, and sucrose. Pi -deficient hps7 roots also produce a high level of reactive oxygen species. Previous research showed that the overexpression of GOLDEN-like (GLK) transcription factors in transgenic Arabidopsis activates photosynthesis in roots. The GLK overexpressing ( GLK OX ) lines also exhibit increased inhibition of root growth under Pi deficiency. The increased inhibition of root growth in hps7 and GLK OX lines by Pi deficiency was completely reversed by growing the plants in the dark. Based on these results, we propose that suppression of photosynthetic gene expression is required for sustained root growth under Pi deficiency.